2022
DOI: 10.1038/s41561-022-00926-1
|View full text |Cite
|
Sign up to set email alerts
|

A century of groundwater accumulation in Pakistan and northwest India

Abstract: The groundwater systems of northwest India and central Pakistan are amongst the most heavily exploited in the world. Groundwater has been monitored in the region for more than a century resulting in a unique long-term record of groundwater level change. Here we present an analysis of post-monsoon groundwater levels from 1900 to 2010. We show that for the majority of the last century groundwater levels were rising and calculate net groundwater accumulation of c.350 km 3 (estimated range: 150-450 km 3 ). Large s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Urbanization can increase local precipitation, but mostly reduces soil permeability and increases runoff intensity. While increased precipitation intensities have enhanced groundwater recharge, most notably in tropical regions (medium confidence), there is high confidence that groundwater depletion has occurred since at least the start of the 21st century, as a consequence of groundwater withdrawals for irrigation in agricultural areas in drylands [28].…”
Section: Increasing Water Cycle Perturbations Due To Human Activitiesmentioning
confidence: 99%
“…Urbanization can increase local precipitation, but mostly reduces soil permeability and increases runoff intensity. While increased precipitation intensities have enhanced groundwater recharge, most notably in tropical regions (medium confidence), there is high confidence that groundwater depletion has occurred since at least the start of the 21st century, as a consequence of groundwater withdrawals for irrigation in agricultural areas in drylands [28].…”
Section: Increasing Water Cycle Perturbations Due To Human Activitiesmentioning
confidence: 99%
“…MacAllister et al. (2022) have shown that in 20th century recharge from canal irrigation networks led to net groundwater accumulation in large transboundary aquifers in Central Pakistan and northwest India. Cuthbert, Taylor, et al.…”
Section: Discussionmentioning
confidence: 99%
“…These rivers are often located in arid climates with flat terrain and extensive groundwater withdrawals. MacAllister et al (2022) have shown that in 20th century recharge from canal irrigation networks led to net groundwater accumulation in large transboundary aquifers in Central Pakistan and northwest India. Cuthbert, Taylor, et al (2019) estimated that the groundwater recharge in sub-Saharan Africa is a predominantly focused type in semi-arid and hyper-arid areas.…”
Section: Implications and Prospectsmentioning
confidence: 99%
“…According to Wada et al (2010), there are various hotspots of groundwater depletion throughout the World, the highest rates of groundwater depletion were observed in North-East Pakistan and North-West India. Several recent studies which are largely using the Gravity Recovery and Climate Experiment satellites data set identified groundwater depletion in Pakistan (Ahmed et al 2019;MacAllister et al 2022). Pakistan is one of the 36 countries under severe water stress, with a projected decrease of 500 cubic meters in water availability per capita.…”
Section: Introductionmentioning
confidence: 99%